ANALISIS PRODUKSI PADI ORGANIK DI KABUPATEN SRAGEN TAHUN 2008 - Novianto, Fajar Widayat; Setyowati, Eni (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
The purpose of this study was to analyze factors influencing the production of organic rice that is land area, seed, labor, fertilizer, and water. This study uses OLS analysis tool (ordinary least squares method). The results show a significant correlation between the variable land area (LH), number of seeds (BH), number of workers (TK), total fertilizer (KDP), and the cost of irrigation (AIR) with organic rice production. Among these five variables is negatively related to variable fertilizer. While the existence of the model test showed that the model exists for use. Land area (LH) has a positive influence on the production of organic rice. The number of seeds (BH) has a positive influence on the production of organic rice, Labor (TK) has a positive influence on the production of organic rice. The use of organic fertilizers (KDP) have an influence on the production of organic rice nagatif. The cost of irrigation (WATER) has a positive influence on the production of organic rice. The results of the classical model assumptions there is no problem, either multicollinearity, heteroscedasticity, specification model, and normality.